Hubungan Kualitas Pelayanan Kesehatan terhadap Loyalitas Pasien Non Asuransi di Rumah Sakit X Purwodadi - Sari, Novita; Desty, Rani Tiara; Anggorowati, Lindra (Universitas Ivet, 2023)
Patient loyalty is a patient's attitude that describes loyalty towards services to utilize health services repeatedly to meet medical service needs. Service quality is one of the factors that influences patient loyalty which includes physical evidence (Tangible), reliability, responsiveness, assurance and empathy. This research aims to determine the relationship between the quality of health services and the loyalty of non-insurance patients who receive services at X Purwodadi Hospital. This research uses quantitative research with a cross-sectional research design, with a total of 100 non-insured patients as respondents. The sampling technique used was accidental sampling. Data analysis was carried out by using the chi square test. The results of the relationship analysis using the chi square test (p<0.05) showed that there was a relationship between physical evidence (p=0.000), reliability (p=0.000), capture power (p=0.000), assurance (p=0.000) and empathy (p=0.000) on non-insurance patient loyalty at X Purwodadi Hospital. Suggestions to hospitals to further improve the quality of service to provide a good perception so as to increase patient loyalty at X Purwodadi Hospital.